Corporate Technological Capability as a Driver to Firm Performance: A Study on Firms Listed at the Nairobi Securities Exchange - Ndungu Samuel Machiri; Margaret Oloko; John Karanja Ngugi; Romanus Odhiambo (Britain International for Academic Research (BIAR) Publisher, 2023)
The aim of this paper was to assess the role played by corporate technological capabilities on firm performance. The ability of a firm to integrate information technology in its operations has been known to be integral in driving organizational success by promoting efficiency and effectiveness. The prevailing underperformance of the listed firms in Kenya raises the question on whether these firms have integrated adequate technology and whether they have what it takes to effectively incorporate technology in their operations, hence the subject of this study. Through a descriptive research design, the study surveyed 240 senior management personnel drawn from the 64 listed firms using a structured questionnaire. The data was analysed using SPSS and Amos software for descriptive statistics and structural equation modelling respectively. The findings revealed that technological capabilities had a significant influence on the performance of firms listed at the NSE (R2 = .096; β = 0.150; P=0.0001<0.05). It was concluded that through adequate ICT infrastructure, ICT human skills and the commitment to integrate and accept use of ICT, the listed firms would strengthen their operational efficiency thus record superior performance.